Transcriptomic and functional analysis provides molecular insights into multicellular trichome development. Issue 1 (16th February 2022) - Dong, Mingming; Xue, Shudan; Bartholomew, Ezra S; Zhai, Xuling; Sun, Lei; Xu, Shuo; Zhang, Yaqi; Yin, Shuai; Ma, Wenyue; Chen, Shuying; Feng, Zhongxuan; Geng, Chao; et al.
Abstract: Trichomes, the hair-like structures located on aerial parts of most vascular plants, are associated with a wide array of biological processes and affect the economic value of certain species. The processes involved in unicellular trichome formation have been well-studied in Arabidopsis ( Arabidopsis thaliana ). However, our understanding of the morphological changes and the underlying molecular processes involved in multicellular trichome development is limited. Here, we studied the dynamic developmental processes involved in glandular and nonglandular multicellular trichome formation in cucumber ( Cucumis sativus L.) and divided these processes into five sequential stages. To gain insights into the underlying mechanisms of multicellular trichome formation, we performed a time-course transcriptome analysis using RNA-sequencing analysis. A total of 711 multicellular trichome-related genes were screened and a model for multicellular trichome formation was developed. The transcriptome and co-expression datasets were validated by reverse transcription-quantitative PCR and in situ hybridization. In addition, virus-induced gene silencing analysis revealed that CsHOMEOBOX3 ( CsHOX3 ) and CsbHLH1 are involved in nonglandular trichome elongation and glandular trichome formation, respectively, which corresponds with the transcriptome data. This study presents a transcriptome atlas that provides insights into the molecular processes involved in multicellular trichome formation in cucumber and can be an important resource for future functional studies. Abstract : Transcriptomic and functional analysis of cucumber ( Cucumis sativus L.) cotyledon trichomes provides a framework for understanding the regulatory network of multicellular trichome formation.